2012
DOI: 10.1111/j.1399-6576.2012.02746.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulse transit time as a quick predictor of a successful axillary brachial plexus block

Abstract: PTT is a reliable, quick and objective method to assess whether axillary block is going to be successful or not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 11 publications
0
17
1
Order By: Relevance
“…Because of this, several studies have been performed. Kortekaas et al ( 22 ) reported that the mean PTT difference increased significantly after a successful axillary brachial plexus blockade. They concluded that PTT is a reliable method to evaluate whether a brachial plexus block is going to be successful.…”
Section: Discussionmentioning
confidence: 99%
“…Because of this, several studies have been performed. Kortekaas et al ( 22 ) reported that the mean PTT difference increased significantly after a successful axillary brachial plexus blockade. They concluded that PTT is a reliable method to evaluate whether a brachial plexus block is going to be successful.…”
Section: Discussionmentioning
confidence: 99%
“…Because reliable non-invasive VTT measurements are difficult, as an alternative we measure the PTT. PTT can be used to assess a successful loco regional block of an extremity [ 9 , 10 ], to monitor vasomotor tone, and for assessment of autonomic nervous system response [ 11 ]. Another non-invasive measurement to estimate the VTT is the pulse wave velocity (PWV).…”
Section: Introductionmentioning
confidence: 99%
“…. Similarly, higher sensitivity and specificity were found for perfusion indices . However, even the simplest study (measuring skin temperature by simple touch) achieved a 92% sensitivity, with a positive predictive value of 95% .…”
Section: Testing Of Onset and Assessing Readiness For Surgerymentioning
confidence: 86%
“…. Other investigators have used measures of perfusion to gauge block success, including pulse transit time and perfusion or flow indices derived from the pulse oximeter .…”
Section: Testing Of Onset and Assessing Readiness For Surgerymentioning
confidence: 99%